In vitro toxicity evaluation of lomefloxacin-loaded MCM-41 mesoporous silica nanoparticles. (4th May 2021) - Tzankova, Virginia; Aluani, Denitsa; Yordanov, Yordan; Valoti, Massimo; Frosini, Maria; Spassova, Ivanka; Kovacheva, Daniela; Tzankov, Borislav
Abstract: Lomefloxacin (LF) is interesting as a model molecule from a safety point of view because of its high potential for serious adverse drug effects (i.e. phototoxic reactions). In this study, MCM-41 mesoporous silica nanoparticles (MCM-41) were loaded with lomefloxacin, aiming to overcome the drug's intrinsic cytotoxicity. The good biocompatibility of the empty drug carrier (0.1–1.0 mg/ml) was established by the absence of red blood cell lysis (hemolysis assay). The cytotoxicity of empty MCM-41 and lomefloxacin-loaded MCM-41 (LF-MCM-41) was evaluated by using a battery of in vitro cytotoxicity assays: Alamar blue, lactate dehydrogenase release and reactive oxygen species formation by dichlorofluorescein assay. Three cell cultures models: hepatoma HepG2, fibroblasts L929 and endothelial EA.hy926 cells were used to compare the cytotoxicity and reactive oxygen species formation by free drug, empty MCM-41, and LF-MCM-41. The findings from the study indicated that empty MCM-41 (0.1–1.0 mg/ml) showed a low cytotoxic potential in HepG2, followed by L929 and EA.hy926 cells. Lomefloxacin loading in MCM-41 mesoporous silica nanocarrier reduced the cytotoxicity of the free lomefloxacin, especially in the high concentration (1.0 mg/ml MCM-41, containing 120 µg/ml LF). L929 and EA.hy926 cells were more sensitive to the protective effects of LF-MCM-41, compared to HepG2 cells. The results indicate that an improvement in lomefloxacin safety might be expected after incorporation in an appropriate drug delivery system.